2018
DOI: 10.1080/21691401.2018.1518910
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional nanogel engineering with redox-responsive and AIEgen features for the targeted delivery of doxorubicin hydrochloride with enhanced antitumor efficiency and real-time intracellular imaging

Abstract: Nanogels exhibit potential application values in drug delivery systems because of their tunable properties and biocompatibility. In this study, multifunctional hyaluronic-based nanogels (HNPs), all-trans retinoid acid (ATRA)/aggregation-induced emission luminogen (AIEgen) fluorophores (TPENH 2)-grafted hyaluronic acid (HA) with disulfide bonds as linkers of (HA-ss-ATRA/TPENH 2), were successfully developed for doxorubicin hydrochloride (DOX) delivery. Besides, the controls of HA-ATRA/TPENH 2 were also develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Higher intracellular accumulation of DOX-loaded HNPs caused significantly higher tumor cell suppression than the control and free drug. An in vitro real-time imaging biodistribution and uptake study of DOX-loaded HNPs exhibited CD44-mediated tumor accumulation and uptake in the tumor cells ( Ma et al, 2018 ). In all the above studies, HA-decorated nanogels exhibited outstanding results which was due to binding of HA specifically to the CD44 receptor which promoted cellular internalization of nanocarriers, leading to release of their cargo into the tumor microenvironment because generally at low pH bonding between HA and its cargo could be broken.…”
Section: Cd44 Engineered Nanocarriers For Cancer Therapymentioning
confidence: 99%
“…Higher intracellular accumulation of DOX-loaded HNPs caused significantly higher tumor cell suppression than the control and free drug. An in vitro real-time imaging biodistribution and uptake study of DOX-loaded HNPs exhibited CD44-mediated tumor accumulation and uptake in the tumor cells ( Ma et al, 2018 ). In all the above studies, HA-decorated nanogels exhibited outstanding results which was due to binding of HA specifically to the CD44 receptor which promoted cellular internalization of nanocarriers, leading to release of their cargo into the tumor microenvironment because generally at low pH bonding between HA and its cargo could be broken.…”
Section: Cd44 Engineered Nanocarriers For Cancer Therapymentioning
confidence: 99%
“…Ma et al [63] reported a multifunctional nanomel gel project with redox reaction and AIEgen characteristics. All-transretinoic acid (ATRA), with a disulfide bond as a linking agent and a group of aggregation induced luminescence (TPENH 2 ) grafted with hyaluronic acid (HA), forms a fluorescent gel HA-ss-ATRA/TPENH 2 HNPs delivery carrier: ATRA as the hydrophobic core of multifunctional hyaluronic acid nanomaterials (HNPs), HA as a hydrophilic agent, using disulfide bond as redox sensitive bonds between HA and ATRA, and preparing HA-ss-ATRA two affinity conjugates, which can control the release of drugs according to the intracellular environment (Figure 11).…”
Section: Drug Deliverymentioning
confidence: 99%
“…(a) Synthesis of HA-ss-ATRA/TPENH 2 conjugate. (b) HA-ss-ATRA/TPENH 2 HNPs is formed and used for drug delivery (reprinted from[63]).…”
mentioning
confidence: 99%
“…A variety of internal and external stimuli, that is, light, magnetism, temperature, enzyme, pH, ultrasonic waves, glucose, and redox potential have been used to get desired response and coordinated drug release . Especially, nanogels releasing therapeutics in response to intracellular redox potential have received considerable interest due to their immediate response capability and applicability in cancer drug delivery . In the past decade, a majority of redox‐responsive matrices have been designed, aiming prolonged circulation time and degradation after cellular internalization.…”
Section: Fabrication Of Redox‐responsive Nanogelsmentioning
confidence: 99%